Biological nitrogen fixation, plant nitrogen demand, and physiological processes involved in seed yield and seed composition in soybeans - Tamagno, Santiago (Kansas State University, 2019)
Soybean [Glycine max (L.) Merr.] plants can capture atmospheric nitrogen (N) through symbiotic relationships with soil bacteria in a process called “biological N fixation” (BNF), reducing the reliance on synthetic fertilizers. To meet growth of the global population and increasing demand for quality protein and oil, the need for soybean will inexorably grow. One of the challenges to further improve soybean seed yield is the high demand of N in comparison to cereals and other oilseed crops. Further characterization of the environmental and management effects on BNF process is needed to enhance its capacity for supplying N to the crop. This dissertation is organized in four chapters outlining these topics through a series of experiments describing the association between plant nutrition, BNF, and seed composition with seed yield generation. Chapter 1 presents a synthesis analysis on a nutrient-based physiological framework on four key variables determining N efficiency in soybean (i.e., seed yield, N seed concentration, total N uptake, and nitrogen harvest index). Results showed that N partitioning to the seeds is the main parameter responsible in seed yield variation instead of N seed concentration. An experiment in Chapter 2 explored the hypothesis of the carbon (C) cost of BNF on biomass production, yield formation, and seed composition. Chapters 3 and 4 explored the historical component behind seed yield generation and seed composition. Results from Chapter 3 describe the shift in allocation of reproductive biomass using the allometric approach, whereas Chapter 4 provides a detailed description of the dynamics of oil and fatty acid accumulation under two N regimes.
Keywords: soybean; nitrogen; protein; oil; biological nitrogen fixation; seed composition